2015
DOI: 10.4236/ajibm.2015.512079
|View full text |Cite
|
Sign up to set email alerts
|

Counterfeit Products and the Role of the Consumer in Saudi Arabia

Abstract: The aim of this paper is to investigate the key antecedents of Saudi consumers' attitudes toward counterfeit products. The study is also set out to examine the relationship of consumers' attitude towards counterfeit product with purchase intention. The study adopted the self-administered survey methodology technique using a pre-validated pre-piloted questionnaire. The questionnaire was adapted from one previously used in Brazil. A survey of 520 respondents was selected in Riyadh market based on convenience-sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Saudi Arabia, a country with a relatively higher per capita income compared to Malaysia, has been an attractive emerging market for pirates and counterfeiters hoping to take advantage of the marketing efforts of others in recent years (Paul, 2014). In Saudi Arabia, Albarq (2015) has found that Saudi consumers' intentions to purchase or not to purchase counterfeit luxury products were due to the influence of several factors including perceived risk, subjective norm, price-quality inference, prior purchase of counterfeits and integrity. The same author further reported that in 2012, the Saudi Customs Department has seized 62 million counterfeit products worth about $50m.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Saudi Arabia, a country with a relatively higher per capita income compared to Malaysia, has been an attractive emerging market for pirates and counterfeiters hoping to take advantage of the marketing efforts of others in recent years (Paul, 2014). In Saudi Arabia, Albarq (2015) has found that Saudi consumers' intentions to purchase or not to purchase counterfeit luxury products were due to the influence of several factors including perceived risk, subjective norm, price-quality inference, prior purchase of counterfeits and integrity. The same author further reported that in 2012, the Saudi Customs Department has seized 62 million counterfeit products worth about $50m.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The same author further reported that in 2012, the Saudi Customs Department has seized 62 million counterfeit products worth about $50m. In combating piracy and counterfeiting of luxury goods, the department has introduced some programs aimed at seizing counterfeit goods at the country's borders before they could be distributed throughout the country (Albarq, 2015;Paul, 2014). Whilst the Saudi Customs Department continues to prevent the import and/or export of counterfeit goods, it does not have any formal and reliable recording system for counterfeit products entering the country (Albarq, 2015).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…It also wastes precious human and financial resources, and constitute an enormous problem facing global pharmaceutical industry [3,4]. The definition and classification of counterfeiting and/or substandard medicines (drugs) which become a worldwide phenomenon is still in continuous updating [3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Although, there is no official reports on the scale of counterfeit medicines distribution in the Saudi market, but in 2014 the number of counterfeit products (electronic, fashion, medicine, foods, cosmetics, etc..) exceeded US$ 62 million in ports [8].…”
Section: Introductionmentioning
confidence: 99%